Book Review: Assessing Social Science Research Ethics and Integrity: Case Studies and Essays - Ugljesa Radulovic (Clinical Sociology Review)
Published in Springer’s Clinical Sociology: Research and Practice series, Assessing Social Science Research Ethics and Integrity: Case Studies and Essays is the work of Harry Perlstadt, Professor Emeritus at Michigan State University’s Department of Sociology. This scholarly work is concerned with research ethics in the social sciences, focusing on the protection of human participants in social experiments. With two comprehensive essays and a meticulous analysis of six contentious experiments, Perlstadt embarks on a journey to elucidate the complex interplay between ethics and empirical inquiry.